Towards Structure-Guided Development of Pain Therapeutics Targeting Voltage-Gated Sodium Channels - Nguyen, Phuong T.; Yarov-Yarovoy, Vladimir (Frontiers in Pharmacology, 2022)
Voltage-gated sodium (NaV) channels are critical molecular determinants of action potential generation and propagation in excitable cells. Normal NaV channel function disruption can affect physiological neuronal signaling and lead to increased sensitivity to pain, congenital indifference to pain, uncoordinated movement, seizures, or paralysis. Human genetic studies have identified human NaV1.7 (hNaV1.7), hNaV1.8, and hNaV1.9 channel subtypes as crucial players in pain signaling. The premise that subtype selective NaV inhibitors can reduce pain has been reinforced through intensive target validation and therapeutic development efforts. However, an ideal therapeutic has yet to emerge. This review is focused on recent progress, current challenges, and future opportunities to develop NaV channel targeting small molecules and peptides as non-addictive therapeutics to treat pain.